Answer:A
Step-by-step explanation:
For SSS you need all sides
<span>△RST is a right triangle because RS¯¯ is perpendicular to RT¯¯ .</span>
Answer:
The value of m is 6.
Step-by-step explanation:
Here, the given equation,
![x^4-(3m+2)x^2+m^2=0](https://tex.z-dn.net/?f=x%5E4-%283m%2B2%29x%5E2%2Bm%5E2%3D0)
![x^4+0x^3-(3m+2)x^2+0x+m^2=0](https://tex.z-dn.net/?f=x%5E4%2B0x%5E3-%283m%2B2%29x%5E2%2B0x%2Bm%5E2%3D0)
Let the roots of the equation are a-3b, a-b, a+b and a + 3b, ( they must be form an AP )
Thus, we can write,
![a-3b+a-b+a+b+a+3b=\frac{\text{coefficient of }x^3}{\text{coefficient of }x^4}](https://tex.z-dn.net/?f=a-3b%2Ba-b%2Ba%2Bb%2Ba%2B3b%3D%5Cfrac%7B%5Ctext%7Bcoefficient%20of%20%7Dx%5E3%7D%7B%5Ctext%7Bcoefficient%20of%20%7Dx%5E4%7D)
![=\frac{0}{1}=0](https://tex.z-dn.net/?f=%3D%5Cfrac%7B0%7D%7B1%7D%3D0)
![\implies a=0----(1)](https://tex.z-dn.net/?f=%5Cimplies%20a%3D0----%281%29)
![(-3b)(-b)+(-b)(b)+(b)(3b)+(3b)(-3b)+(-b)(3b)+(-3b)(b)=\frac{\text{coefficient of }x^2}{\text{coefficient of }x^4}}](https://tex.z-dn.net/?f=%28-3b%29%28-b%29%2B%28-b%29%28b%29%2B%28b%29%283b%29%2B%283b%29%28-3b%29%2B%28-b%29%283b%29%2B%28-3b%29%28b%29%3D%5Cfrac%7B%5Ctext%7Bcoefficient%20of%20%7Dx%5E2%7D%7B%5Ctext%7Bcoefficient%20of%20%7Dx%5E4%7D%7D)
![=\frac{-3m-2}{1}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-3m-2%7D%7B1%7D)
![3b^2-b^2+3b^2-9b^2-3b^2-3b^2=-3m-2](https://tex.z-dn.net/?f=3b%5E2-b%5E2%2B3b%5E2-9b%5E2-3b%5E2-3b%5E2%3D-3m-2)
![-10b^2=-3m-2](https://tex.z-dn.net/?f=-10b%5E2%3D-3m-2)
![\implies b^2=\frac{3m+2}{10}-----(2)](https://tex.z-dn.net/?f=%5Cimplies%20b%5E2%3D%5Cfrac%7B3m%2B2%7D%7B10%7D-----%282%29)
![(-3b)(-b)(b)(3b)=\frac{\text{Constant term}}{\text{coefficient of}x^4}= m^2](https://tex.z-dn.net/?f=%28-3b%29%28-b%29%28b%29%283b%29%3D%5Cfrac%7B%5Ctext%7BConstant%20term%7D%7D%7B%5Ctext%7Bcoefficient%20of%7Dx%5E4%7D%3D%20m%5E2)
![9b^4=m^2](https://tex.z-dn.net/?f=9b%5E4%3Dm%5E2)
![9(\frac{3m+2}{10})^2=m^2](https://tex.z-dn.net/?f=9%28%5Cfrac%7B3m%2B2%7D%7B10%7D%29%5E2%3Dm%5E2)
![9(\frac{9m^2+4+12m}{100})=m^2](https://tex.z-dn.net/?f=9%28%5Cfrac%7B9m%5E2%2B4%2B12m%7D%7B100%7D%29%3Dm%5E2)
![81m^2+36+108m=100m^2](https://tex.z-dn.net/?f=81m%5E2%2B36%2B108m%3D100m%5E2)
![-19m^2+108m+36=0](https://tex.z-dn.net/?f=-19m%5E2%2B108m%2B36%3D0)
![19m^2-108m-36=0](https://tex.z-dn.net/?f=19m%5E2-108m-36%3D0)
![19m^2-114m+6m-36=0](https://tex.z-dn.net/?f=19m%5E2-114m%2B6m-36%3D0)
![19m(m-6)+6(m-6)=0](https://tex.z-dn.net/?f=19m%28m-6%29%2B6%28m-6%29%3D0)
![(19m+6)(m-6)=0](https://tex.z-dn.net/?f=%2819m%2B6%29%28m-6%29%3D0)
![\implies m=-\frac{6}{19}\text{ or }m=6](https://tex.z-dn.net/?f=%5Cimplies%20m%3D-%5Cfrac%7B6%7D%7B19%7D%5Ctext%7B%20or%20%7Dm%3D6)
But m > 0,
Hence, the value of m is 6.
Answer:
42.42in³
Step-by-step explanation:
This problem bothers on the mensuration of solid shapes, a cone
Step one
We know that the volume of a cone is
V= 1/3πr²h
Given data
Diameter d= 6 inches
Radius r= diameter/2= 6/2= 3 inches
Height h = 4.5 inches
Step two
Substituting our given data we have
Volume = 1/3*3.142*3²*4.5
V= 1/3*3.142*9*4.5
V= 127.251/3
V= 42.42in³